2015
DOI: 10.1002/pc.23565
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and simulation of the electrical properties of CNTs/epoxy nanocomposites for high performance composite matrices

Abstract: Carbon fiber composite laminates have good electrical properties due to the performance of the fibers, but the composite anisotropy induces a quite lower conductivity through the thickness. In fact, in this direction the fiber bundles are separated by insulating epoxy matrix. In this work, CNTs (carbon nanotubes) with different geometries and functionalization have been added to an epoxy resin to improve the electrical performance. The nanofilled matrix has been used to produce carbon fiber (CF) composites for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…Analysis performed in Refs. [ 19 , 20 , 21 ] has shown that such a disagreement is caused by the existence of non-ideal contacts between the nanotubes forming the percolation chain. The contact resistance usually exceeds the typical resistance of nanotubes by several orders of magnitude.…”
Section: Percolation Behavior Of Polymer-based Composites Doped Wimentioning
confidence: 99%
See 2 more Smart Citations
“…Analysis performed in Refs. [ 19 , 20 , 21 ] has shown that such a disagreement is caused by the existence of non-ideal contacts between the nanotubes forming the percolation chain. The contact resistance usually exceeds the typical resistance of nanotubes by several orders of magnitude.…”
Section: Percolation Behavior Of Polymer-based Composites Doped Wimentioning
confidence: 99%
“… Points: Dependence of the empirical parameter k , determining the degree of non-linearity of conduction of reduced GO samples on the annealing temperature. Line: The result of calculation within the frame of the percolation model of conduction [ 20 ]. …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…All the proposed models can be classified in the four following main categories based on distinct approaches: (1) statistical, which predicts the conductivity using percolation theory. The base of these models is on the probability of particle content into the matrix that is, early modes develops by Kirkpatrick and Zallen , (2) thermodynamic models which developed mainly based on Mamunya studies focus on the filler and polymer surface energies as well as polymer melt viscosity, among others. Since this model shows dependency of electrical behavior on the polymer–filler interaction, the size and the filler amounts, are taken into account in this study which will be further explained in the following sections, (3) geometrical percolation models which are originally proposed for prediction of the conductivity of sintered mixtures of conducting and insulating powders .…”
Section: Modelingmentioning
confidence: 99%
“…Epoxy resin (EP) is a material with excellent properties, which is widely used in semiconductor equipment manufacturing [ 1 , 2 , 3 ], adhesives [ 4 , 5 ], aerospace [ 6 , 7 , 8 ] and other fields. Epoxy resin based on the diglycidylether of bisphenol A (DGEBA) exhibited good mechanical and thermal properties, high chemical and corrosion resistance properties as well as excellent adhesion properties because of the presence of hydroxyl and epoxy groups of EP.…”
Section: Introductionmentioning
confidence: 99%